Tail-spillover effects between African currencies, bitcoin, gold and oil during two recent black swan events - Thobekile Qabhobho; Cwayita Mpuku; Izunna Anyikwa; Andrew Phiri (Cogent Business & Management, 2024)
Since the onset of the COVID-19 pandemic, African currencies, cryptocurrencies, and commodity markets have undergone significant fluctuations, displaying fat-tail properties that lies at the outer ends of the normal probability curve. The recent Russia-Ukraine war has further disrupted these markets, generating considerable interest among academics and practitioners. Our study delves into tail-end returns and volatility connectedness between Bitcoin, crude oil, gold, and four African currencies amidst the COVID-19 and Russia-Ukraine war. Employing a quantile vector autoregressive (QVAR) approach, we analyze tail-end spillover effects between markets from 4 November 2019, to 7 September 2022. Our findings reveal heightened connectedness at the quantile ends of co-movements, with left-tail spillovers being more pronounced for returns, while right-tail spillovers dominate for volatility. Bitcoin, and to a lesser extent gold and oil, emerge as effective tail-ended hedges for the Egyptian Pound and Nigerian Naira but not for other African currencies like the Algerian Dinar and South African Rand. Consequently, users of Egyptian and Nigerian currencies in international financial markets can seek hedging opportunities in traditional cryptocurrencies and commodities during recent Black Swan events, unlike those using South African and Algerian currencies. Additionally, our results suggest limited diversification benefits associated with (i) currencies linked to oil-exporting or oil-importing countries, (ii) currencies linked to Shariah-compliant financial systems, but do indicate diversification benefits in high-inflation environments. These findings hold relevance for investors seeking improved hedging strategies against African currency risk and for African policymakers aiming to enhance intra-continental trade, foreign direct investment, and cross-border business expansions.
Keywords: G2; O43; 650; Bitcoin; gold; oil; african currencies; quantile connectedness; black swan events